Differences in symptoms of depression in comparison to the course of diabetes with diabetic foot complications - Mladenovic, Danilo; Milanovic, Ana; Latas, Milan (Engrami, 2025)
Introduction: Diabetes is a significant global health challenge, with increasing prevalence worldwide. The poorly understood relationship between physical complaints and mental health, manifested through associated depressive symptoms in people with diabetes, has attracted considerable attention in recent years. The aim: To examine the relationship between the presence of depressive symptoms and diabetic foot complications in people with diabetes. Method: The study used a retrospective-prospective design and was conducted in the period from October 15, 2023. until 15.02.2024. years. A total of 87 subjects with diabetes were included, who were categorized into three groups based on the presence of diabetic foot complications - diabetic ulcer. The first group consisted of patients with diabetic foot and ulcer treated by amputation (DS/A) (n = 29), the second group consisted of patients with diabetic foot and ulcer treated conservatively (DS/K) (n = 30), and the third the group consisted of patients with diabetes who did not have a diabetic foot (DS-cont) (n = 28). By examining the medical records, the following data were collected: age, sex, number of comorbid diseases, duration of the disease in years. All patients completed the PHQ-9 questionnaire to assess depressive symptoms. Results: Patients from the DS/Amp group had significantly higher PHQ-9 scores compared to patients from the DS/K and DM-cont groups. Linear regression analysis identified group affiliation as a significant predictor of increased PHQ-9 scores. Conclusion: People with diabetic foot amputations show higher levels of depressive symptoms. Further prospective studies are needed to clarify the cause-and-effect relationship between the presence of depressive symptoms and diabetic foot complications. Keywords: diabetic foot, depressive symptoms, amputations, comorbidity.